Monolithically integrated dual‐lock‐in optical sensor. Issue 4 (1st February 2014) - Davidovic, M.; Seiter, J.; Hofbauer, M.; Gaberl, W.; Zimmermann, H.
Abstract : A single‐pixel sensor consisting of a dual‐lock‐in amplifier with an innovative dual‐cathode photodetector is presented. The sensor is fabricated in 0.35 µm CMOS and is designed to be integrated in a multipixel array working with a frequency shifted feedback (FSF) laser. The realised single‐pixel structure occupies an area of 120 × 100 µm² at a 58% fill factor. This pixel ensures frequency detection of the optical signal independently of its phase and power. The bandwidth of the interleaved pin photodiodes is larger than 100 MHz even for 850 nm. The sensor shows a dynamic range of ∼24 dB at a modulation frequency of 10 MHz. Signals up to 35 MHz can be detected.